Development of renal atrophy in murine 2 kidney 1 clip hypertension is strain independent. (August 2016) - Kashyap, Sonu; Boyilla, Rajendra; Zaia, Paula J.; Ghossan, Roba; Nath, Karl A.; Textor, Stephen C.; Lerman, Lilach O.; Grande, Joseph P.
Abstract: The murine 2-kidney 1-clip (2K1C) model has been used to identify mechanisms underlying chronic renal disease in human renovascular hypertension. Although this model recapitulates many of the features of human renovascular disease, strain specific variability in renal outcomes and animal-to-animal variation in the degree of arterial stenosis are well recognized limitations. In particular, the C57BL/6J strain is considered to be resistant to chronic renal damage in other models. Our objectives were to determine strain dependent variations in renal disease progression and to identify parameters that predict renal atrophy in murine 2K1C hypertension. We used a 0.20 mm polytetrafluoroethylene cuff to establish RAS in 3 strains of mice C57BL/6 J ( N = 321), C57BLKS/J ( N = 177) and129Sv ( N = 156). The kidneys and hearts were harvested for histopathologic analysis after 3 days or after 1, 2, 4, 6, 7, 11 or 17 weeks. We performed multivariate analysis to define associations between blood pressure, heart and kidney weights, ratio of stenotic kidney/contralateral kidney (STK/CLK) weight, percent atrophy (% atrophy) and plasma renin content. The STK of all 3 strains showed minimal histopathologic alterations after 3 days, but later developed progressive interstitial fibrosis, tubular atrophy, and inflammation. The STK weight negatively correlated with maximum blood pressure and % atrophy, and positively correlated with STK/CLK ratio. RAS produces severe chronic renal injury in the STK of all murine strains studied, including C57BL/6J. Systolic blood pressure is negatively associated with STK weight, STK/CLK ratio and positively with atrophy and may be used to assess adequacy of vascular stenosis in this model.